Regulation of t he Concentration in t he Extraction and Distillation Aggregate - Abdurakhmonova M.I.; Sharipova N.R. (Genius Journals, 2022)
This article discusses the technology of extraction of vegetable raw materials for the complete extraction of oils. The issue of process automation in the extraction-distillation unit is also being solved. According to the existing theory, the preparation of raw materials for pressing is to destroy the cell of oilseeds as much as possible. The extraction of essential oils from plant materials is based on extraction with organic solvents or steam distillation. This allows a significant loss of volatile aromatic substances and leads to a violation of the natural balance of the components in the composition of essential oils.
Keywords: process; extraction; distillation; automatization